2018
DOI: 10.1159/000488404
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac-Specific Overexpression of Silent Information Regulator 1 Protects Against Heart and Kidney Deterioration in Cardiorenal Syndrome via Inhibition of Endoplasmic Reticulum Stress

Abstract: Background/Aims: Increased endoplasmic reticulum (ER) stress contributes to development of cardiorenal syndrome (CRS), and Silent Information Regulator 1 (SIRT1), a class III histone deacetylase, may have protective effects on heart and renal disease, by reducing ER stress. We aimed to determine if SIRT1 alleviates CRS through ER stress reduction. Methods: Wild type mice (n=37), mice with cardiac-specific SIRT1 knockout (n=29), or overexpression (n=29), and corresponding controls, were randomized into four gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…In support of our results, previous related studies have shown that SIRT1 plays a crucial part in the regulation of ER stress-related apoptosis in different cells [2023]. Moreover, SIRT1-deficient cells are sensitive to oxidative stress [52, 53], further proving the idea that SIRT1 plays an essential role in protecting against oxidative stress and related apoptosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In support of our results, previous related studies have shown that SIRT1 plays a crucial part in the regulation of ER stress-related apoptosis in different cells [2023]. Moreover, SIRT1-deficient cells are sensitive to oxidative stress [52, 53], further proving the idea that SIRT1 plays an essential role in protecting against oxidative stress and related apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…SIRT1 exerts antiapoptotic function through the deacetylation of apoptosis-inducible nonhistone proteins including P53 [17], forkhead family proteins [18], and RelA/p65 subunit of nuclear factor- κ B (NF- κ B) [19]. Previous studies verified the protective role of SIRT1 in different cells under oxidative stress and ER stress [2023]. In osteoarthritis cartilage, research showed that the activation of SIRT1 is essential to the maintenance of articular cartilage homeostasis owing to its antiapoptotic effect [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that cardiac myocytes are vulnerable to cellular ER stress and contribute to the pathogenesis of several cardiovascular derangements through exposure to hyperoxidation, inflammation, apoptosis, etc. These findings have sparked interest, demonstrating a link between ER stress and cardiovascular pathogenesis, while the elevation of ER stress–associated apoptosis has been proposed to contribute to various cardiovascular diseases (Camargo et al, 2018; Chang et al, 2018; Huang et al, 2018). Hence, modulation of ER stress, especially downstream of calcium-mediated apoptotic execution pathways, becomes critical in understanding the mechanism and the development of a novel target of pathogenesis of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…31−34 More directly, as a consequence of HIF-1a expression, mRNA expression of VLDLr and the proapoptotic transcription factor CHOP are also increased, and by the end of this process, CHOP upregulates bcl-2-like protein 11 mRNA expression and activates Bax protein to translocate from the cytosol to the mitochondria. 31,35 Our results demonstrate that cold ischemia and graft storage activated all these participants, starting from higher SERCA1 protein levels reflecting an increased Ca 2+ pump function in the ER and elevated HIF-1a expression in cardiomyocytes. In addition, higher intracellular Ca 2+ can activate GSK-3b, the proapoptotic factor in the intrinsic mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 67%